2004
DOI: 10.1016/j.eurpsy.2004.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of somatic and anxiety symptoms which contribute to the detection of depression in primary health care

Abstract: Somatic symptoms and anxiety symptoms are often disregarded in the detection of depression in primary care. The present investigation examined to what extent somatic and anxiety symptoms recorded with the Composite International Diagnostic Interview-Primary Health Care Version (CIDI-PHC) can improve the detection of depression as compared to the General Health Questionnaire-12-item version alone. Data from the World Health Organization study on Psychological Problems in General Health Care were used. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 44 publications
1
17
0
3
Order By: Relevance
“…1 The relation between the SAS and its factors and depression may be expected given that prior research suggests that somatic symptoms (i.e., back pain, feelings of heaviness/lightness in parts of the body, periods of bodily weakness, fatigue, and tension) are significantly correlated with depression (e.g., Goldberg, 1996). Prior research has also shown that somatic complaints significantly contribute to the onset (e.g., Barkow et al, 2004) and course (e.g., Wilson, Widmer, Cadoret, & Judiesch, 1983) of depression. However, examination of individual SAS items, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…1 The relation between the SAS and its factors and depression may be expected given that prior research suggests that somatic symptoms (i.e., back pain, feelings of heaviness/lightness in parts of the body, periods of bodily weakness, fatigue, and tension) are significantly correlated with depression (e.g., Goldberg, 1996). Prior research has also shown that somatic complaints significantly contribute to the onset (e.g., Barkow et al, 2004) and course (e.g., Wilson, Widmer, Cadoret, & Judiesch, 1983) of depression. However, examination of individual SAS items, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In primary care, somatic symptoms play an important role in the manifestation of depressive disorders (11) . Because this has been under-evaluated, clinical case review is not an adequate methodology to establish prevalence rates of mental disorders in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…31 Los estudios en pacientes con TDM que comparan algunas poblaciones Latinas viviendo en sus países de origen como Colombia, Perú y Puerto Rico versus población no Latina de Estados Unidos, muestran índices de somatización usualmente mayores en las poblaciones de Latinoamérica a pesar de tasas de síntomas depresivos similares.…”
Section: Resultsunclassified